ANALISIS YURIDIS PERLINDUNGAN PENGUNGSI DI JALUR BALKAN PADA MASA PANDEMI COVID-19 PASCA KEBIJAKAN PENOLAKAN PENGUNGSI OLEH KROASIA - Muhammad Rusdiansyah; Zulfikar Jayakusuma; Evi Deliana HZ (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
At the end of 2020 the DRC (Denish Refugee Council) issued a reportthat the Croatian border security had taken action against refugees. Theuncontrolled condition of Covid-19 is the reason Croatia has refused the entryof refugees. As a participating country in The Convention Relating to theStatus of Refugees 1951, Croatia has an obligation to comply with existingregulations, including the prohibition against turning away refugees asstipulated in Article 33 paragraph 1. However, the Covid-19 pandemic hascaused Croatia to reject the entry of refugees. This has an impact on theresponsibility of providing protection to refugeesThe type of this research is normative research using literature studiesin searching for data. This research is descriptive by using the existing rulessynchronization method. In this study using qualitative methods in analyzingthe data that has been collected by the author. The data used is secondary datain the form of codified rules.The results of this study explain that the responsibility to provideprotection for refugees has changed to become the responsibility of UNHCR.This is because the condition of Covid-19 in Croatia has an impact onCroatia's inability to carry out its obligations as a participating country to the1951 Convention. The form of protection that can be provided to refugees isin the form of implementing the UNHCR program, namely Human Assistanceto protect refugees in the Balkans. the author's suggestion, namely theimplementation and implementation of the UNHCR mandate to protectrefugees, and the increase in cooperation between countries through theBalkan route and also UNHCR in implementing human assistance programsto protect refugees during the Covid-19 pandemic.Keywords: Croatia, Refugee, Covid-19